Anesthetic management of mini sternotomy and excision of mediastinal neurogenic tumor: Brain–Heart crosstalk - Arnab Paul; Joseph N Monteiro; Uday Gandhe; Gargi Deshpande (Annals of Cardiac Anaesthesia, 2023)
Brachial plexus tumors are rare and pose challenges for neurosurgeons due to their anatomical complexity. Retrosternal extension of a tumor makes it more difficult for the surgeons as well as for the anesthesiologists to secure a definitive airway. A cardiopulmonary bypass would be lifesaving in the event of acute cardiorespiratory decompensation. Multidisciplinary collaboration and cooperation between the neurosurgeon, oncosurgeon, cardiothoracic surgeon, and anesthesiologist are imperative to ensure good patient outcomes. Meticulous preoperative evaluation and operative planning are essentially the key factors in anesthetic management. Here we report a successful management of a 49-year-old male patient presented with a large painless mass arising from his right supraclavicular region and compressing the roots of the brachial plexus, trachea, and esophagus and extending up to the apex of the lungs, posted for mini sternotomy and excision of the mass.